The Relationship Between Gadget Use And Stress Levels On Adolescent Sleep Quality - Nirmala , Fifi; Azim, La Ode Liaumin; Yuliskartika, Yuliskartika; Hartoyo, Agnes Mersatika (Politeknik Kesehatan Kemenkes Mamuju, 2025)
One of the problems of today's adolescents is the lack of fulfillment of quality sleep which has an impact on a decrease in the cognitive level of young people. In Indonesia, adolescents who experience sleep quality disturbances are in a fairly high category, where several research results show that more than 30% of adolescents experience poor sleep quality. One of the factors that causes adolescents to experience poor sleep quality includes lifestyle changes including the use of gadgets. This study aims to determine the relationship between gadget use and stress levels on sleep quality in adolescents at SMP Negeri 10 Kendari in 2022. This type of research is analytic using a Cross Sectional Study design. The population in this study were all students of class VIII SMP Negeri 10 Kendari, totaling 202 people, while the number of samples was 133 obtained using the lambeshow formula. Samples were drawn using the Proportionate Stratified Random Sampling technique. The measuring instrument used was the Pittsburgh Quality Index (PSQI) questionnaire (to measure sleep quality) while stress was measured by a questionnaire (Depression Anxiety Stress Scale 42). Of the 133 respondents, most were teenagers with poor sleep quality, 79 respondents (59.4%) had good sleep quality, 54 respondents (40.6%). The results of the analysis of the relationship obtained the relationship between gadget use and sleep quality (p = 0.000), duration of gadget use (p = 0.000), activity using gadgets (p = 0.000, stress (p = 0.004). The results of this study provide evidence that the use of gadgets, the duration of gadget use, the activity of using gadgets and stress are related to the sleep quality of adolescents at SMP Negeri 10 Kendari in 2022